2002
DOI: 10.1034/j.1398-9995.2002.23664.x
|View full text |Cite
|
Sign up to set email alerts
|

The link between allergic rhinitis and allergic asthma: A prospective population‐based study. The Copenhagen Allergy Study

Abstract: Background: It has been hypothesized that allergic rhinitis and allergic asthma are manifestations of the same disease entity. We aimed to investigate the relationship between allergic rhinitis and allergic asthma.Methods: Participants in a population‐based study of 15–69‐year‐olds in 1990 were invited to a follow‐up in 1998. A total of 734 subjects were examined on two occasions eight years apart. Allergic rhinitis to pollen was defined as a history of nasal symptoms on exposure to pollens and IgE specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
1
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(220 citation statements)
references
References 26 publications
13
194
1
12
Order By: Relevance
“…This was confirmed in 2014 by Ciprandi and colleagues, stating that patients showing bronchial hyperresponsiveness had significantly more frequent mite allergy (11). In the same way, Linneberg and coworkers reported asthma in 25% of patients with allergic rhinitis who were pollen-sensitive and in 50% of those patients who were mite-sensitive or animal-sensitive (12). Ciprandi demonstrated that bronchial hyperresponsiveness was present in 50% of seasonal allergic rhinitis patients and in 70% of patients experiencing perennial symptoms (13).…”
Section: Implication For Diagnosis and Therapeutic Managementsupporting
confidence: 57%
See 2 more Smart Citations
“…This was confirmed in 2014 by Ciprandi and colleagues, stating that patients showing bronchial hyperresponsiveness had significantly more frequent mite allergy (11). In the same way, Linneberg and coworkers reported asthma in 25% of patients with allergic rhinitis who were pollen-sensitive and in 50% of those patients who were mite-sensitive or animal-sensitive (12). Ciprandi demonstrated that bronchial hyperresponsiveness was present in 50% of seasonal allergic rhinitis patients and in 70% of patients experiencing perennial symptoms (13).…”
Section: Implication For Diagnosis and Therapeutic Managementsupporting
confidence: 57%
“…Allergic rhinitis and asthma are airways diseases that often occur concomitantly. Epidemiological evidence from studies conducted in industrialized countries show that 60 to 98.9% of asthmatics patients have concomitant rhinitis and that 20 to 40% of rhinitics patients show clinical evidence of asthma (12,(21)(22)(23)(24).…”
Section: Bronchial Hyperresponsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of asthma in subjects without rhinitis is usually <2%. The prevalence of asthma in patients with rhinitis varies from 10% to 40% depending on the study (67,(1882)(1883)(1884). Patients with a sensitization to indoor and outdoor allergens are more prone to have asthma as a co-morbidity than those with indoor or outdoor allergy (1883).…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%
“…2-4 Atopic dermatitis and allergic rhinitis in children have been reported to be significant risk factors for subsequent development of asthma. [5][6][7] The treatment of allergic diseases is based on allergen avoidance, pharmacological treatment and immunotherapy. In the pharfmacological therapy of atopic dermatitis, only symptomatic anti-inflammatory and anti-allergic treatments, local or systemic, exist.…”
Section: Introductionmentioning
confidence: 99%